2016
DOI: 10.1097/inf.0000000000001073
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylaxis After Immunization of Children and Adolescents in Germany

Abstract: This study confirms that anaphylaxis after immunization in children and adolescents is a rare event. AS03 adjuvanted A/H1N1 pandemic influenza vaccine seems to be associated with a higher risk of anaphylaxis when compared with other vaccines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…A recent study 98 investigated the annual frequency of anaphylaxis following immunization, a rare AE which can be life-threatening and causes hospitalization within 48 hours after immunization. The study was conducted on subjects younger than 18 years in Germany between June 2008 and May 2010.…”
Section: Vaccine Types and Production Methodsmentioning
confidence: 99%
“…A recent study 98 investigated the annual frequency of anaphylaxis following immunization, a rare AE which can be life-threatening and causes hospitalization within 48 hours after immunization. The study was conducted on subjects younger than 18 years in Germany between June 2008 and May 2010.…”
Section: Vaccine Types and Production Methodsmentioning
confidence: 99%
“…are a known and reported adverse event related to immunization, 13 but such events are exceedingly rare, occurring after <1 per million doses of vaccines administered. 23,[82][83][84][85] Guillain-Barré syndrome suspected as a [161][162][163] MMR = measles, mumps, rubella; MMRV = measles, mumps, rubella, varicella; DTaP= diphtheria, tetanus and acellular pertussis; Tdap = tetanus, diphtheria and acellular pertussis; OPV = oral polio vaccine; HPV = human papilloma virus FIGURE 3 Disseminated papular rash after receipt of smallpox vaccine (ACAM2000), without detectable intralesional virus 37 vaccine-associated event through case reports. 36,86,87 Symptoms include progressive neuromuscular weakness, usually beginning in the extremities and then centrally, with potential progression toward respiratory failure or cranial nerve weakness.…”
Section: Guillain-barré Syndromementioning
confidence: 99%
“… 10 Also in Germany, except for the influenza A virus subtype (H1N1) pandemic influenza vaccination, it was estimated at 6.8 cases per year. 11 In the previous study 2009–2013 in Korea, vaccines had been reported being responsible for 1.0 percent of the cases. 12 However, this was limited in identifying the frequency of vaccine anaphylaxis because it was a report by a small number of medical institutions and the result was a code analysis using the International Classification of Diseases, 10th Revision (ICD-10), but not a BCCD based analysis.…”
Section: Discussionmentioning
confidence: 96%
“…In the US, anaphylaxis by inactivated trivalent influenza vaccine and monovalent were 1.35 and 1.83 per million doses, respectively, and in Germany, anaphylaxis was most common after the immunization of the pandemic H1N1 influenza vaccine. 10 11 One study found that seven out of 10 cases of vaccine anaphylaxis were caused by influenza vaccines in Korea. 12 …”
Section: Discussionmentioning
confidence: 99%